Unternehmen „Hermann” — pacyfikacja Puszczy Nalibockiej z perspektywy SS-Sonderbataillon Dirlewanger - Kuberski, Hubert (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The participation of the SS-Sonderbataillon Dirlewanger in the pacifications of the partisan movement in occupied Belarus remains a topic that, despite some discussion in Polish, Russian, English and German sources, demands further scholarly attention. The article brings into focus the events taking place in the summer of 1943 in the German-occupied territory of the Nowogródek and Wilno Voivodeships of the prewar Republic of Poland, which were included the German-occupied General District of Belarus (Generalbezirk Weißruthenien/Генеральная акруга Беларусь) during the war. The anti-partisan operation (Unternehmen “Hermann”) carried out by the Germans with the participation of units consisting of Germans, Austrians, Belarusians, Lithuanians, Latvians and Ukrainians was directed against the Soviet and Polish partisans. Of course, apart from the extensive use documents of German archives, we drew attention to documents of Polish and Soviet provenance, and in particular to the memories of Polish witnesses inhabiting the area of Naliboki Forest. The aim of this article is to present the latest scope of research on the activities of the SS-Sonderbataillon Dirlewanger in comparison with other counter-insurgency (anti-partisan) units carrying out ruthless pacification measures as part of “Bandenbekämpfung”.
Keywords: Oskar Dirlewanger; SS-Sonderbataillon Dirlewanger; Bandenbekämpfung; Kampfgruppe von Gottberg; Waffen-SS; niemiecka okupacja Białorusi; partyzantka sowiecka; Armia Krajowa